REPRODUCTIVE PERFORMANCE OF HATCHERY-BRED, WILD-CAUGHT BROODSTOCK, AND THEIR OUTBREED OF THE AFRICAN CATFISH Clarias gariepinus (Burchell, 1822) - Victor Oscar Eyo; Felix Eze; Ochuko Joshua Eriegha (Indonesian Aquaculture Journal, 2020)
This study was conducted to evaluate the reproductive performance of hatchery-bred and wild-caught broodstock of Clarias gariepinus. Thirty pairs of each hatchery-bred and wild-caught broodstock (15 females and 15 males) was used for the study. Induced breeding was carried out in four groups with three replications at a ratio of 1:1 by hypophysation method. Group A: hatchery-bred male and hatchery-bred female (HBM m + HBF f); B: wild-caught male and wild-caught female (WCM m + WCF f), C: hatchery-bred female and wild-caught male (HBF f+ WCM m) and D: wild-caught female and hatchery-bred male C. gariepinus (WCF f + HBM m). Results showed that egg diameter, sperm motility, sperm density, and male GSI were not significantly different (P>0.05) whereas ovary weight, sperm volume, fecundity, female GSI, and percentage fertilization were significantly higher (P<0.05) in hatchery-bred broodstock than wild-caught broodstock. Hatchability was significantly higher (P<0.05) in Group C and D than A and B. In conclusion, a better reproductive performance in C. gariepinus with an economic advantage could be recorded through the combination of wild-caught and hatchery-bred broodstock.